EFFECT OF HERBICIDES ON GROWTH, GRAIN YIELD AND QUALITY OF BARLEY - Mustafa J. Al-Khafaji; S. M. A. Safi; W. F. Hammood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to study the effect of herbicide (lintur @180 g.ha-1 + Axial @1.5 L.ha-1, Navigator @ 1.25 L.ha-1 and the control treatment) in the companion weeds. Besides, grain yield and its components of three cultivars of barley (IPA 99, Buhooth 256, Aldebaran). The experiment was carried out according to RCBD, within split plot arrangement using three replicates. The cultivars represented the Main-plots, while herbicides and control treatments represented the sub-plots. The second included a laboratory experiment with four replicates of 50 seeds per replicate to study some grain quality characteristics resulting from the first field experiment. The results were showed the superiority of the Buhooth 256 cultivar in number of spikes, weight of 1000 grains, and the grain yield with an average of 495.10 spike.m-2, 22.23 g, and 1.46 ton.ha-1, respectively. Buhooth 256 also recorded the best results in increasing the percentage of weed control, reducing weed dry weight, and increasing the inhibition ratio. The same cultivar exceeded in most characteristics of grain quality. The treatment of herbicides (lintur + Axial) exceeded by achieving the highest average number of spikes of (471.60 spike.m-2), and the highest number of grains per spike with (51.77 grain.spike-1). Coupled with the weight of 1000 grains (21.47 g), and the highest grain yield (1.53 ton.ha-1).